PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI AKADEMIK (SIAKAD) DI PRODI TEKNOLOGI INFORMASI BERBASIS WEBSITE UNTUK MENINGKATKAN SKALABILITAS - sapitri, rani; Marsehan, Ahmad; Rohmadin, Abdul Hadi (J-ENSITEC, 2025)
The rapid development of information technology has encouraged educational institutions to undergo digital transformation to enhance efficiency and effectiveness in academic data management. This study discusses the design and implementation process of a web-based Academic Information System at the Information Technology Study Program, Universitas PGRI Silampari. The main objective of the system development is to replace manual processes that are often inefficient and error-prone, as well as to integrate currently fragmented systems. The research methodology includes needs analysis, system design, implementation, and comprehensive testing using a structured software development approach. The implementation results show that the system significantly improves the efficiency of academic administration, accelerates student data processing, and provides accurate, real-time access to academic information. Furthermore, the system supports scalability, allowing it to accommodate the growing number of students each year. It also simplifies academic reporting processes, making it easier for administrators to manage academic data. In conclusion, the web-based academic information system offers an effective solution to support the improvement of academic service quality in higher education institutions.